Effects of relaxation technique along with aerobic training and aerobic training alone on quality of life in asthmatic children: a comparative study - Gaikwad, Pratibha; Wadia, Farzeen; Asgaonkar, Bharati; Ghodke, Paneri (International Journal of Research in Medical Sciences, 2021)
Background: The current study focuses on the comparative effects of 12 weeks Jacobson’s progressive muscle relaxation technique as an intervention along with aerobic training and aerobic training alone on quality of life in asthmatic children. Methods: For this, 60 the asthmatic children were screened based on the inclusion criteria and were divided into two groups (30 each). Group A included Jacobson’s relaxation along with aerobic training and Group B included aerobic training alone. Conventional physiotherapy treatment was given to both the groups. Quality of life was assessed using Paediatric asthma quality of life questionnaire. Exercise capacity was measured using six minute walk test distance, peak expiratory flow rate by the mini wright peak flow meter and rate of perceived exertion by Borg’s scale. Results: Data analysis revealed that there was a statistical and clinical significant improvement in all the three domains of QOL in Group A when compared to Group B. However, Relaxation along with aerobic training and aerobic training alone both had equal effects in improving six minute walk test distance, peak expiratory flow rate and rate of perceived exertion in Group B. Conclusions: Thus it can be concluded that in asthmatic children with mild to moderate severity, a 12 week protocol of Jacobson’s relaxation along with aerobic training should be in cooperated for better results.